2008
DOI: 10.1093/jee/101.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Cotesia flavipes (Hymenoptera: Braconidae) in Sugarcane Fields of Ethiopia and Origin of Founding Population

Abstract: Cotesia flavipes (Cameron) (Hymenoptera: Braconidae) is used as a classical biological control agent against Chilo partellus (Swinhoe) (Lepidoptera: Crambidae), a serious exotic pest of cereal crops in eastern and southern Africa. This parasitoid has been introduced into several African countries for the control of C. partellus in maize, Zea mays L., and sorghum, Sorghum bicolor (L.), but it has never been released in Ethiopia. It is hypothesized that it spread into Ethiopia from populations released in Kenya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Evidence of the establishment and spread following the release of biological control agents has been highlighted in several studies and surveys (Assefa et al, 2008;Cugala, 2007;Getu et al, 2003;Mailafiya et al, 2011;Moonga, 2007;Omwega et al, 1995Omwega et al, , 1997Omwega et al, 2006;Sallam et al, 2001). In addition, the parasitism-effect and suppression-effect of the released biological control agents has been demonstrated and confirmed the effectiveness in reducing pest densities (Cugala, 2007;Jiang et al, 2006;Zhou et al, 2001).…”
Section: Released Bio-agents For Control Of Cereal Stemborers In Eastmentioning
confidence: 87%
See 1 more Smart Citation
“…Evidence of the establishment and spread following the release of biological control agents has been highlighted in several studies and surveys (Assefa et al, 2008;Cugala, 2007;Getu et al, 2003;Mailafiya et al, 2011;Moonga, 2007;Omwega et al, 1995Omwega et al, , 1997Omwega et al, 2006;Sallam et al, 2001). In addition, the parasitism-effect and suppression-effect of the released biological control agents has been demonstrated and confirmed the effectiveness in reducing pest densities (Cugala, 2007;Jiang et al, 2006;Zhou et al, 2001).…”
Section: Released Bio-agents For Control Of Cereal Stemborers In Eastmentioning
confidence: 87%
“…With the GIS coordinates of all the release points, we modelled the spread around each release point in the four cardinal directions using concentric circles respecting the year of release and the appropriate specific annual dispersal rate (Gichini et al, 2008;Nordblom et al, 2002). Omwega et al (1997) found the dispersal rate of C. flavipes to be 60 km per year whereas Assefa et al (2008) found it to be higher than 200 km per year. Later, Omwega et al (2006) estimated this dispersal distance to be 11.23 km per year.…”
Section: Measuring Dispersal Area Of the Bc Agentsmentioning
confidence: 99%
“…The existence of these large continuous populations implies gene flow over long distances and therefore either large dispersal abilities or stable resource availability over large areas. In Africa, C. flavipes , belonging to the same species complex as C. sesamiae, has a dispersal rate estimated to range between 11 and 200 km per year based on biocontrol release and recapture experiments (Assefa, Mitchell, Conlong, & Muirhead, ; Omwega, Muchugu, Overholt, & Schulthess, ). Such dispersal abilities would explain the large population distribution observed in C. sesamiae .…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, C. flavipes, belonging to the same species complex as C. sesamiae, has a dispersal rate estimated to range between 11 and 200 km per year based on biocontrol release and recapture experiments (Assefa, Mitchell, Conlong, & Muirhead, 2008;Omwega, Muchugu, Overholt, & Schulthess, 2013 (Dupas et al, 2008), which has driven adaptive divergence and resulted in speciation in the case of C. typhae.…”
Section: Cotesia Flavipes Species Complexmentioning
confidence: 99%
“…are important larval parasitoid of various lepidopteran insect pest. C. flavipes is used against Chilo partellus [13]. Chelonus sp.…”
Section: Discussionmentioning
confidence: 99%